Implementasi Teknologi Blockchain dalam Aplikasi E-Voting Berbasis Mobile - Restu Aji, Setiawan; Trisari Harsanti Putri, Wahyuningdiah (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2023)
Voting is a key element in democratic processes and decision-making in various contexts. With the development of information technology, traditional voting methods have undergone a significant transformation with the introduction of e-voting systems. Although some previous research has successfully developed e-voting applications, some significant drawbacks have been identified, such as insufficient security issues, risk of manipulation, and reliance on a central authority. Blockchain technology is decentralized and immutable. Therefore, it is an attractive solution in addressing these challenges. This research aims to overcome the weaknesses of previous e-voting applications by developing a mobile-based e-voting application that uses blockchain technology. This research also enables wider voter participation through mobile devices, improving the security and integrity of votes. The use of React Native allows the application to be accessible on various mobile platforms, including Android and iOS. This research has three important aspects: the use of blockchain technology to address security and integrity issues, the development of Mobile-Based e-voting applications to improve accessibility, and the contribution to the development of blockchain applications in various election contexts.